2005
DOI: 10.1111/j.1348-0421.2005.tb03697.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial RNase E‐Associated Proteins

Abstract: RNase E was originally discovered as an RNA-processing enzyme (1). Later it was found that its gene, rne, and ams (altered messenger stability) are identical (7,23,31), suggesting a key role for RNase E in bacterial mRNA processing and decay. Subsequent studies revealed that RNase E controls the stability of many (8, 9), if not most, mRNAs in Escherichia coli (3), as well as being involved in the processing of 5S and 16S rRNAs (1,20,32), tRNA precursors (19) and degradation of small regulatory RNAs (21). Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…Indicated are the delta, beta, alpha and gamma branches of proteobacteria. For the species marked with an asterisk, association of RNase E with one or more degradosome components was confirmed experimentally (Ait- Bara & Carpousis, 2010 ;Erce et al 2009Erce et al , 2010Hardwick et al 2010 ;Jäger et al 2001 ;Kovacs et al 2005 ;Purusharth et al 2005 ;Yang et al 2008). Within gammaproteobacteria, Enterobacteriales, Pasteuralles and Vibrionales are predicted to have an E. coli type of degradosome, while Aeromonadales and Alteromonadales degradosomes lack enolase (Ait- Bara & Carpousis, 2010).…”
Section: Summary and Perspectivementioning
confidence: 91%
“…Indicated are the delta, beta, alpha and gamma branches of proteobacteria. For the species marked with an asterisk, association of RNase E with one or more degradosome components was confirmed experimentally (Ait- Bara & Carpousis, 2010 ;Erce et al 2009Erce et al , 2010Hardwick et al 2010 ;Jäger et al 2001 ;Kovacs et al 2005 ;Purusharth et al 2005 ;Yang et al 2008). Within gammaproteobacteria, Enterobacteriales, Pasteuralles and Vibrionales are predicted to have an E. coli type of degradosome, while Aeromonadales and Alteromonadales degradosomes lack enolase (Ait- Bara & Carpousis, 2010).…”
Section: Summary and Perspectivementioning
confidence: 91%
“…These studies revealed that, similar to their E. coli counterpart, RNase E/G homologues can interact with PNPase in Streptomyces [55] and are able to co-purify with GroEL and metabolic enzymes in Mycobacteria [56]. The specific role of these polypeptides in RNA metabolism and the degree, to which their interaction with RNase E/G is conserved in Actinobacteria, remains to be established.…”
Section: Enzymes With Major and Ancillary Functions In Mrna Turnovmentioning
confidence: 99%
“…36) Another study has suggested that the mycobacterial RNase E/G homolog forms a degradosome-like complex. 37) These two studies suggest that the mycobacterial RNase E/G is functionally related to E. coli RNase E. S. coelicolor also has one RNase E/G homolog, which complemented both the E. coli rne-1 and the rng::cat mutation. 29,30) Bacillus subtilis has no RNase E/G homolog.…”
Section: Discussionmentioning
confidence: 99%